Issues of Exercising the Right to Defence amid the Explanations of the Plenum of the Supreme Court of the Russian Federation - Oksana A. Voltornist (Сибирское юридическое обозрение, 2016)
The article analyzes the explanations of the Plenum of the Supreme Court No. 29 dated June 30, 2015 “On application of laws by the courts ensuring the right to defense in criminal proceedings”. The author details the applied aspects of certain provisions of the aforementioned document within the criminal procedure legislation and estimates their significance for the judicial and investigative practice.